First Molecular and Phylogenetic Identification of Toxoplasma Gondii in Sheep Liver Intended for Human Consumption in Northern Tunisia - Amdouni, Yosra; Hammami, Inés; Farhat, Nadia; Rekik, Mourad; Gharbi, Mohamed (Springer, 2024)
The aim of this study was to estimate the molecular infection prevalence of Toxoplasma gondii in sheep liver tissues destined for human consumption. A total number of 224 liver tissues were collected from slaughtered sheep in Sejnane slaughterhouse (Northwest Tunisia). PCR was used to detect T. gondii DNA in liver tissues followed by phylogenetic analysis of amplicons. The phylogenetic tree was then constructed to compare the partial sequences of the ITS1 gene with GenBank sequences.